Análise de desempenho de um motor ciclo Otto com biogás - Machado, Deisi Oliveira (Universidade do Vale do Rio dos Sinos, 2014)
This study aimed to analyze a generator set equipped with an Otto-cycle combustion engine operating with biogas. In addition, it was an objective to perform a comparative analysis between this system and other one using gasoline as fuel. The tests were performed in a Branco generator, model B4T-5000 BIO, mono cylinder, with the generator charge variation performed through a resistance bench. Performed analysis contemplates electric power generated by the equipment, specific consumption, efficiency, rate of heat transfer in the cogeneration and its effectiveness, λ factor, CO and O2 emissions. The results showed that is possible to obtain electric power through a clean fuel, but the system presented low efficiency. The results of O2 and λ indicate that the combustion is performed with excess air to all configuration and the CO emissions for the biogas were lower than 900 ppm whereas for the gasoline the CO emissions were around 17.400 ppm for the compression rate of 10.2:1 and 70.500 ppm for the rate of 8.2:1.
Keywords: Motor Otto; Biogás; Cogeração; Otto engine; Biogas; Emissions; ACCNPQ::Engenharias::Engenharia Mecânica